From status to sustainability: How social influence and sustainability consciousness drive green purchase intentions in luxury restaurants - Jamid Ul Islam; George Thomas; Norah Ali Albishri (Acta Psychologica)
In today's marketing landscape, consumer demand for eco-friendly products is on the rise, yet the psychological factors that encourage green purchasing intentions remain unclear. To address this research gap, the current study builds on Social Identity Theory to explore the role of social influence and sustainability consciousness in shaping customers' green purchase intentions. Data were collected through a survey of 406 customers at Saudi Arabian upscale restaurants and analyzed using structural equation modeling. The findings reveal that social influence positively impacts both sustainability consciousness and green purchase intentions. Besides, the study identifies sustainability consciousness as a critical mediator in this relationship, emphasizing the importance of intrinsic motivations in driving environmentally responsible behavior. Additionally, gender differences were also examined, revealing that women are more responsive to social influences regarding sustainability consciousness and green purchase intentions. This study enriches the literature by providing a robust framework to understand the collective social processes influencing green consumption. Practically, the research offers actionable insights for managers to develop targeted marketing campaigns, leverage social influencers, and utilize technology to enhance transparency and trust in sustainable practices. This study not only bridges literature gaps but also provides a foundation for promoting green consumption patterns essential for addressing global environmental challenges.